Synergistically complex social well-being: The trust factor - S. A. Kravchenko (RUDN journal of Sociology)
In recent decades, the social has acquired a synergistically complex nature (N.I. Lapin), which is caused both by objective determinants of the dynamic development of social, natural and technological realities, potentially increasing the production of various goods and services, and by subjective meanings of the quality of life - in their materialization, an increasing role belongs to the trust factor. Its study is determined by the civilizational crisis of trust, and its underlying causes are rooted in the formation of a qualitatively new “order out of chaos” (I. Prigogine) and in the staging of “mythical narratives” of the desired, “idealized” social well-being (J. Alexander), the false meanings of which destroy traditional values and dehumanize social relations. Under such challenges and scientific approaches to their analysis, the author designs a nationally oriented model of synergistically complex social well-being, based on the system of trust rooted in the genotype of national culture. This model includes the functional basic institutional structures of society, reproduction of traditional values of interpersonal trust, and implementation of humanistically oriented modernization. Under disequilibrium, risks and vulnerabilities, these components ensure the viability and sustainability of this type of well-being. For its sociological diagnostics, humanistically oriented interdisciplinarity is proposed, organically including both new theories of chaos, complexity and nonlinearity, and humanistic concepts of the sovereign national sociology.